Utilization of Activated Charcoal from Sawdust as an Antibiotic Adsorbent of Tetracycline Hydrochloride - Gatut Ari Wardani; Ega Maulana Qudsi; Anindita Tri Kusuma Pratita; Keni Idacahyati; Estin Nofiyanti (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2021)
The use of activated charcoal from sawdust as an adsorbent of tetracycline hydrochloride compounds has been successfully carried out. Sawdust activated charcoal was carbonized at 450°C for 40 minutes with a charcoal size of 100 mesh and activated using H3PO4 solution. The characteristics of active sawdust charcoal showed that water content, iodine adsorption, and methylene blue adsorption had met SNI 06-3730-1995 regarding technical activated charcoal. Testing the morphology of charcoal using a Scanning Electron Microscope showed that the charcoal pores were opened through the activation process. In the functional group analysis test using infrared spectroscopy, the active group contained in charcoal after being activated contained carbon atoms that were purer than sawdust. The adsorption process of tetracycline hydrochloride using sawdust activated charcoal is known to follow Ho orPseudo second-order (K = 0.0039 g/mg.min), while the adsorption isotherm follows the Langmuir equation, KL = 0.0076 L/mg and adsorption capacity amounting to 242.1307 mg/g. Thermodynamically, the adsorption process occurs not spontaneously with a Gibbs free energy value of 120.8949 kJ/mol and occurs by chemisorption.